Language resources to be used in teaching of LSP and specialised translation: Annual Reports in the banking sector as ad-hoc parallel and comparable corpora, in English, French and Greek - TZIAFA, ELENI (International Journal of Language, Translation and Intercultural Communication, 2016)
This study investigates the use of corpora in teaching of LSP and specialised translation, summarising the findings of the analysis of Annual Reports in the banking sector in English, French and Greek. The objectives of this study are: i. to connect texts and translations from these three languages, whereas English, serving as an intermediate language will help us make the proper choices of terms in Greek and French financial choices, based on informed choices of professional translators, ii. to prepare teaching materials tailored to the communication needs of students of economics or participants of business English courses, as a result of a contrastive linguistic research on the basis of parallel and comparable corpora. For this purpose, we apply easy to use and appealing concordance programs, so that teachers and learners are not put off from working with corpora because the software is too complex or not user-friendly enough. Both teachers and learners would profit a lot more from getting their hands on corpora themselves.